Spacing and Stressing Extracting of Sentences System - Peerach Ngodngamjaras; Napatrapee Teethawatthanakorn; Anuntapat Anuntachai (My University, 2024)
Word stressing and spacing to convey the meaning is an important part of speaking English. Audiences are more likely to engage with a speaker who uses proper word stress and spacing. Stress can be observed from louder pronunciation, and higher frequency. Space can be observed from breathing and the length of time before starting a new sentence. These things, if those who would like to practice English are inexperienced or do not listen to native speakers often, they may not be able to remember the points of stressing and spacing correctly. As a result, speech does not flow smoothly. Nowadays, there are no tutorials or visualizations that clearly point out where the spacing is. For this reason, the organizer decided to create a program that would identify word stress and spacing to display on a dashboard that would be developed into a website in the future.
Keywords: Handwritten Text Recognition Techniques; Natural Language Processing Techniques